(untitled) (Journal of Bangladesh Academy of Sciences, 2009)
The concentration profile surfaces of Phosphorus (P) atoms in Ga-melt in front of the growing GaP crystal under normal conditions of liquid phase epitaxy has been constructed three-dimensionally using the two-dimensional numerical simulation technique. The concentration contours of P atoms inside the solution at different experimental conditions have been constructed along the distance perpendicular to the substrate. The growth rate and the thickness of the grown layer of GaP have been estimated along the distance perpendicular to the substrate for different cooling rates, time and temperatures of growth using the concentration gradient existing at the interface. The temperature contours in the melt have also been constructed by solving an appropriate two-dimensional heat equation for different cooling rates and growth temperatures. Our simulated values have been compared with the experimentally reported values. doi: 10.3329/jbas.v32i1.2446 Journal of Bangladesh Academy of Sciences, Vol. 32, No. 1, 87-95, 2008